MODEL SISTEM DINAMIK UNTUK KEBERLANJUTAN DANAU BATUR, BATUR UNESCO GLOBAL GEOPARK, BALI - Utama, I Putu Wira; Arthana, I Wayan; Nuarsa, I Wayan; Suryawan Wiranatha, Agung (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 18 No 1 (2024)DO - 10.24843/EJES.2024.v18.i01.p01, 2024)
This research aims to analyze the best scenario for conserving Lake Batur, Batur UNESCO Global Geopark (BUGG), Bali. Using the system dynamics method, key factors in the management of Lake Batur can be identified. Based on modeling results, it is known that the sustainability of Lake Batur is strongly influenced by aspects of land use, the environment, the economy, and the social culture of the community. The main leverage factors in supporting the preservation of Lake Batur are law enforcement and supervision, government assistance, as well as training and outreach to the community. The analysis of the sensitivity value of the optimistic/moderate ratio shows that the optimistic scenario is the best option to reduce the lake pollution index to 0.86 (still below the 1 threshold). Increasing community income per capita in this area in 2045 is estimated to reach Rp87.992.747,76/year, with predictions of 9,312 floating net cage plots owned by 2,592 entrepreneurs. The predicted number of plots is 14.90 ha, which is still below 1% of the area of Lake Batur. Keywords: System Dynamics; Sustainability; Lake Batur; BUGG